Westonci.ca is the Q&A platform that connects you with experts who provide accurate and detailed answers. Discover in-depth answers to your questions from a wide network of professionals on our user-friendly Q&A platform. Connect with a community of professionals ready to provide precise solutions to your questions quickly and accurately.

Drag each tile to the correct box. Not all tiles will be used.

Arrange the steps to solve this system of linear equations in the correct sequence.
[tex]\[
\begin{array}{l}
x+y=-2 \\
2x-3y=-9
\end{array}
\][/tex]

1. Multiply the first equation by 3 to get [tex]$3x + 3y = -6$[/tex].
2. Subtract [tex]$3x + 3y = -6$[/tex] (obtained in step 1) from [tex]$2x - 3y = -9$[/tex] to solve for [tex]$x$[/tex].
3. Substitute the value of [tex]$x$[/tex] in the first equation [tex]$(x + y = -2)$[/tex] to get [tex]$y = 1$[/tex].
4. The solution for the system of equations is [tex]$(-3, 1)$[/tex].

Unused tiles:
[tex]\[
x = -15
\][/tex]


Sagot :

To solve the given system of linear equations:
[tex]\[ \begin{array}{l} x + y = -2 \\ 2x - 3y = -9 \end{array} \][/tex]

Follow these steps in the correct sequence:

1. Substitute the value of [tex]\( x \)[/tex] from the first equation [tex]\( (x + y = -2) \)[/tex] to solve for [tex]\( y \)[/tex].

2. Solve for [tex]\( y \)[/tex].

3. The solution for the system of equations is [tex]\((-3, 1)\)[/tex].

Now, let's substitute the steps:

1. Substitute the value of [tex]\( x \)[/tex] from the first equation [tex]\( (x + y = -2) \)[/tex] to solve for [tex]\( y \)[/tex]:
[tex]\[ x = -2 - y \][/tex]

2. Substitute [tex]\( x = -2 - y \)[/tex] into the second equation [tex]\( (2x - 3y = -9) \)[/tex]:
[tex]\[ 2(-2 - y) - 3y = -9 \][/tex]
Simplify and solve for [tex]\( y \)[/tex]:
[tex]\[ -4 - 2y - 3y = -9 \\ -5y - 4 = -9 \\ -5y = -5 \\ y = 1 \][/tex]

3. Substitute [tex]\( y = 1 \)[/tex] back into the first equation [tex]\( (x + 1 = -2) \)[/tex]:
[tex]\[ x + 1 = -2 \\ x = -2 - 1 \\ x = -3 \][/tex]

Thus, the solution for the system of equations is [tex]\( (x, y) = (-3, 1) \)[/tex].

So, the correct final step is:
- The solution for the system of equations is [tex]\((-3, 1)\)[/tex].